Interpreting the Early Modern World
XXII, 246 p.
Keywords: Although historical archaeologists often explore similar themes, the intellectual traditions in the United States and the United Kingdom lead to differing interpretations of these themes. The contributions to this innovative volume provide a bridge between a US-based archaeologist and a UK-based archaeologist on the themes of landscape studies, urban archaeology, memory and memorialization, gender studies, the lives of industrial workers, and archaeological biographies. The chapters are not meant to stand in isolation, but rather provide a dialog between both groups. This work explores the strengths of interpretive historical archaeology in the US and the UK, as well as compare and contrast differing approaches. It aims to foster debate and productive collaborations between historical archaeologists from different geographic regions. It will of interest to UK and US-based archaeologists, as well as those performing interpretive historical archaeology in other regions who will benefit from the insights it provides.